(untitled) (Research, Society and Development, 2024)
Introduction: Endometriosis, especially in its deep infiltrative form, is a chronic disease that negatively affects women’s quality of life, causing debilitating symptoms and impacting various personal spheres. Among the most serious manifestations, deep intestinal endometriosis requires, in some cases, intestinal resection surgery, an approach that can relieve symptoms but also entail significant complications. Objective: To investigate the quality of life of women with intestinal endometriosis who underwent intestinal resection surgery. Methodology: This is an integrative review, with a search carried out from July to October 2024, in the PUBMED, Scielo, and Lilacs databases, using the descriptors: “quality of life” and “endometriosis”. Initially, we had 1,532 publications. Next, 130 were selected by titles and abstracts, and 47 after reading in full. Results: Bowel resection for endometriosis is feasible and effective in improving gastrointestinal and gynecological symptoms and patients’ quality of life, with low long-term complication and recurrence rates. Comparative studies suggest that the laparoscopic approach is a favorable option over open surgery, offering fewer complications and better fertility outcomes, especially for advanced-stage endometriosis. These data reinforce the need for detailed preoperative planning and comprehensive counseling since the quality-of-life assessment can serve as a complementary index in the indication and success of treatments for endometriosis. Conclusion: Intestinal resection offered significant improvements in the quality of life of women with intestinal endometriosis.